Local Turbulent Energy Dissipation Rate in a Vessel Agitated by a Rushton Turbine - Šulc Radek; Pešava Vít; Ditl Pavel (Chemical and Process Engineering)
The scaling of turbulence characteristics such as turbulent fluctuation velocity, turbulent kinetic energy and turbulent energy dissipation rate was investigated in a mechanically agitated vessel 300 mm in inner diameter stirred by a Rushton turbine at high Reynolds numbers in the range 50 000 < Re < 100 000. The hydrodynamics and flow field was measured using 2-D TR PIV. The convective velocity formulas proposed by Antonia et al. (1980) and Van Doorn (1981) were tested. The turbulent energy dissipation rate estimated independently in both radial and axial directions using the one-dimensional approach was not found to be the same in each direction. Using the proposed correction, the values in both directions were found to be close to each other. The relation ε/(N3·D2) ∞ const. was not conclusively confirmed.